The Hell-or-High-Water Clause in Aircraft Leasing Contract: UNIDROIT Principles and the Indonesian Civil Code - Karami, Ahmad Adib; Amalia, Prita; Trisnamansyah, Purnama (Uti Possidetis: Journal of International Law, 2024)
This research analyses the hell-or-high-water clause in aircraft leasing contracts in the context of the principle of freedom of contract. Focusing on the review of the principle of freedom of contract based on UNIDROIT Principles of International Commercial Contract (UPICC) 2016 and Indonesian Civil Code,  this research uses normative juridical method with analytical descriptive approach. The findings show that the hell-or-high-water clause has a high binding force, providing legal certainty, especially for the lessor. However, its application must be in line with the principle of freedom of contract regulated in UPICC 2016 and the Civil Code. The application of this clause is suggested to consider three limitations stipulated by the UPICC 2016: first, the principle of freedom of contract that allows businesses to choose partners and transaction terms; second, the exclusion of certain sectors in the public interest by the state; and third, mandatory rules that limit the content of the contract. Therefore, the hell-or-high-water clause should be applied with due regard to the implementation of the principle of freedom of contract as well as national law or the existence of compelling national regulations.